Patologi Sosial dalam Novel Bendera Setengah Tiang Karya Annisa Lim - Lestari, Ajeng Puri; Setiawan, Heru; Munifah, Siti (LEKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Abstract Social pathologi is any behavior that is contrary to the norms that apply in society. This study aims to describe the forms of social pathology, factors causing social pathology, the impact of social pathology. This type of research is descriptive qualitative research that focuses on data collection in the form of writing. In this research, the data collection techniques uses the reading and note-taking method. Data analysis technique used is from Miles Huberman in the form of data collection, data reduction, data presentation, and drawing conclusions. The object of research uses a novel manuscript entitled Bendera Setengah Tiang by Annisa Lim which will be published by Coconut Books in 2022. The results obtained in this study are found in various forms of social pathology, namely the pathology of criminality, corruption, gambling, prostitution, and mental disorder. Criminality in the form of brawls, sexual, harassment, teror threats, kidnappings, persecution, and murders. In addition, the are also various factors and impacts caused by social pathology. The forms of social pathology contained in the novel Bendera Setengah Tiang were analyzed using Kartini Kartono’s theory. Keywords: Social Pathology, Novel, Literary Sociology